2013
DOI: 10.1002/psp.1773
|View full text |Cite
|
Sign up to set email alerts
|

European Liaisons? A Study on European bi‐national Marriages in Belgium

Abstract: European bi-national marriages as a special case of interethnic unions have received relatively little attention in research. Existing studies on interethnic marriage mainly orient on union formation among non-western migrants and in particular intermarriages between the majority group and non-western migrants, which are often perceived as indicators for integration. European intermarriages can nonetheless be of similar interest from the perspective of European integration and identity formation. In this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…For example, a study by Bratsberg, Raaum, and Sørlie (2007) of immigrants in Norway showed that the probability of return migration is high during the first five years after arrival, but decreases quickly thereafter. One of the key indicators of integration is, however, whether an immigrant marries a member of the host country, as marriage is an important aspect of social integration (Alba and Nee 2003;Koelet and de Valk 2013;van Ham and Tammaru 2011). The integrative benefits of intermarriage include, for example, that the immigrant tends to learn the host country language and absorb the unwritten rules of the society more quickly, and that he or she is helped in establishing a position in the labour market (Dribe and Lundh 2008;Ellis, Wright, and Parks 2004;Kantarevic 2004;Meng and Meurs 2009).…”
Section: Integration and Return Migration: A Negative Relationshipmentioning
confidence: 99%
“…For example, a study by Bratsberg, Raaum, and Sørlie (2007) of immigrants in Norway showed that the probability of return migration is high during the first five years after arrival, but decreases quickly thereafter. One of the key indicators of integration is, however, whether an immigrant marries a member of the host country, as marriage is an important aspect of social integration (Alba and Nee 2003;Koelet and de Valk 2013;van Ham and Tammaru 2011). The integrative benefits of intermarriage include, for example, that the immigrant tends to learn the host country language and absorb the unwritten rules of the society more quickly, and that he or she is helped in establishing a position in the labour market (Dribe and Lundh 2008;Ellis, Wright, and Parks 2004;Kantarevic 2004;Meng and Meurs 2009).…”
Section: Integration and Return Migration: A Negative Relationshipmentioning
confidence: 99%
“…Just under half (47%) of the foreign-born population has European citizenship, representing 7% of the total population, and their importance is still growing (Pelfrene, 2014). Sixty-four per cent of married or cohabiting European migrants in Belgium live with a native partner (Koelet and De Valk 2014). All in all a perfect case country for the study of European migrants.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to the broader category of marriages between different social units, general terms such as “exogamy,” “heterogamy,” “intermarriage,” “cross-border marriage,” or “mixed marriage” are used. More specifically, depending on the nature of the contextual boundaries as mentioned above and listed in brackets in Figure 1, marriages across borders may be referred to as “international” (Jones and Shen, 2008; Piper, 1997), “binational” (Irastorza and DeVoretz, 2015; Koelet and de Valk, 2014), “transnational” (Charsley, 2012; Williams, 2012), “cross-national” (Baker, 1990; Cretser, 1999), “cross-border” (e.g. Constable, 2012; Lee, 2012; Wang and Chang, 2002), “intercultural” (Cools, 2006; Sharaievska et al., 2013), “cross-cultural” (Falicov, 1995), “interethnic” (Bizman, 1987; Burma, 1963; Furtado and Theodoropoulos, 2011; Lee et al., 1974), “interracial” (Barnett, 1963; Gevrek, 2014; Monahan, 1970), “interreligious” (Burchinal and Chancellor, 1963; Chancellor and Monahan, 1955), or “interfaith” (Cila and Lalonde, 2014).…”
Section: Different Conceptualizations and Measures Of “Intermarriage”mentioning
confidence: 99%
“…'intercultural' in Psychology versus 'binational', 'international' or 'transnational' in Referring to the broader category of marriages between different social units, general terms such as 'exogamy', 'heterogamy', 'intermarriage', 'cross-border marriage' or 'mixed marriage' are used. More specifically, depending on the nature of the contextual boundaries as mentioned above and listed in brackets in Figure 1, marriages across borders may be referred to as 'international' (Jones and Shen, 2008;Piper, 1997), 'binational' (Irastorza and DeVoretz, 2015;Koelet and de Valk, 2014), 'transnational' (Charsley, 2012;Williams, 2012), 'cross-national' (Baker Cottrel, 1990;Cretser. 1999), 'cross-border' (e.g.…”
Section: Different Conceptualizations and Measures Of 'Intermarriage'mentioning
confidence: 99%